Thresholds between ficction and history in Memórias of Branca Dias, of Miguel Real - Souza, Aldinida de Medeiros; Araújo, Andréia Rafael de (Revista Desassossego, 2019)
The historiographical metafiction allows authorship to give "wing" for the myths, elaborating characters with greater or less critical reflection in the narratives. The present essay is a study that starts from the relationship between Literature and History in the novel Memórias de Branca Dias (2009), by Miguel Real, in order to analyze the protagonist of this novel. The real figure of Branca Dias has become a myth, legends have around this name; is a character in presentia, in some fictions, in absentia in others. We seek to identify, based on A construção da Personagem Romanesca (2008), by Cristina Vieira, elements that show a critical-reflexive discourse by the authorship of Miguel Real, which allows us to recall Branca Dias as a woman of struggle, because the novel, in addition to making it possible to return to colonial Brazil, shows the iron hand of the Catholic Church in the period of the Inquisition, against which Branca fought her entire life.